Impacto de alterações físico-climáticas sobre a resposta hidrossedimentológica de uma bacia semiárida: uso do Modelo SWAT - soil and water assessement tool - Araújo Neto, José Ribeiro (2017)
For the prediction of the impacts of anthropic actions and climatic changes on the hydrossedimentological processes the distributed and physically based models have been quite effective. Using SWAT (Soil and Water Assessment Tool) in a semi-arid watershed and nested sub-basins with different soil uses, this study aimed to evaluate the impacts of soil management and climate change on water and sediments. The study area is composed of a representative Semiarid Basin Experimental in Iguatu, Ceará (BEI), presenting 14.72 km2 and two micro-scale EIB nested sub-basins with areas ranging from 0.01 to 0.03 km2 and with different uses of the soils denominated: Dry Tropical Forest (FTS) - representing the Caatinga Forest and Deforestation, Burning and Pasture (DQP). The study period included hydrosedimentological collections between the years of 2013 and 2017, making a total of five years of study. With the application of SWAT, a suitable model was found suitable for hydrosedimentological simulations in a semi-arid basin, with Nash-Sutcliffe coefficients (NSE) for the EIB approximately 0.50 for the calibration and superior to 0, 80 for validation. The validation of the model at stations upstream of the calibration section showed that the model also represents from reasonable to very good the water and sediment flows along the nested FTS and DQP sub-basin scales. The SWAT model presented better predictive performance of water flows and sediments for events with rainfall of magnitude equal to or greater than 30 mm, representing a total of 75.3% of the hydrossedimentological flows. Soil use scenarios showed that the vegetation cover with open FTS presented water losses due to surface runoff and soil losses due to water erosion slightly lower than the other scenarios due to the higher herbaceous stratum present in the control of erosive processes. The current use + recovery scenario of riparian forest with open FTS was shown to be the most efficient in terms of water retention and sediment in the EIB basin. The scenarios that contemplate anthropic action, expansion of agricultural use or pasture are those that cause greater increase in surface runoff and sediment production. The increase of the land use expansion in a hypothetical scenario in which the whole EIB basin is occupied by dense FTS causes a gradual increase and with a linear tendency in the hydrossedimentological responses in the basin. The analysis of land use expansion shows that the impacts of preservation are less than the impacts caused by the increase of degradation activities in the basin. Future scenarios of climate change show a worrying result regarding the availability of water resources in the Brazilian semi-arid region, a drastic reduction in surface runoff was observed for the simulation period (2046-2064) both in the EIB basin and in the sub- and FST and DQP nests, reaching values ranging from 30% to 98% of the runoff reduction for the different evaluated models of climate change. Similar trend of reduction in sediment flows for the different scenarios of climate change were also verified, considering that as the runoff presents a reduction, sediment transport is also directly reduced